Recurrent black stains and periodontal disease - Ratika Lihala; Deepika Jayaprakash; Praveen Jayaram; A N Savitha; Anirban Chatterjee; M Rajini (Wolters Kluwer Medknow Publications, 2019)
Objectives: The objective of this study was to identify the anaerobic pigment-forming bacteria present in black stain and correlate its occurrence with dental caries incidence and periodontal destruction. Materials and Methods: A total of 50 healthy subjects with the chief complaint of recurrent black stains were selected based on the inclusion and exclusion criteria. decayed/missing/filled surfaces score, community periodontal index, Gingival Crevicular Fluid (GCF), black stain score, and microbial analysis were done. Results: The data presented indicate that black stain has a constant microflora, dominated by various gram-negative rods, gram-positive cocci and rods (P ≤ 0.1). However, the incidence of gram-positive rods decreased with the increase in plaque score and probing depths and decrease in black stain score. Conclusions: Presence of black stains is predominated by various gram-positive and negative rods, and gram-positive cocci. Increase in the plaque score decreases the severity of black stains, thereby increasing the probability of periodontal destruction and dental caries incidence in adult subjects. Further studies are required to corroborate the results.